BASES OF ELEMENTARY ARITHMETICS IN GALOIS’S FIELDS - Petryshyn, Lubomyr (International Journal of Computing, 2014)
It is resulted the theoretical bases and structure of facilities for transformation and digital processing of messages in the Galois code systems and proved efficiency of their application in comparison with the known methods of binary coding. The lacks of implementation dynamics of arithmetic operations in binary codes and methods of their elimination are analyzed at the Galois code and increasing of digital processing speed.